Internationalization project cocktail team in-depth analysis Denmark - Sousa, Miguel Cabral Meneses de Almeida e (2023)
The aim of this paper is to pave the way for the internationalization a Cocktail Team, a Portuguese firm operating in the bar consulting industry. With this in mind an analysis of the Portuguese market for this sector was conducted as well as a firm analysis to assess their current situation and readiness for the project. Furthermore, multiple countries were analyzed, and four in-depth analyses were conducted resulting in the UK being chosen as the target market with the creation of an entry plan, involving a marketing and financial plan. A literature review was also conducted to complement the report.